2008
DOI: 10.1080/19396360801952078
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Effects of Methamphetamine Repeated Dosing on Proliferation and Apoptosis of Rat Germ Cells

Abstract: Methamphetamine (MAMP) is a central nervous system stimulant that is increasingly abused especially by teenagers and young adults, a group in its reproductive age. MAMP effects on the male reproductive system are not clear. In this experimental study, we evaluated the effects of MAMP administration on proliferation and apoptosis in seminiferous tubules of rat testis. Methamphetamine hydrochloride was synthesized by iodination of norephedrine hydrochloride and reduction to methamphetamine. Mature male rats were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 18 publications
2
24
0
Order By: Relevance
“…The effects of MA on sperm chromatin also appear to be dose-depended as similar drugs which had more negative effects in high doses. Our findings were similar to the study by Alavi and colleagues which have demonstrated that frequent consumption of high dosage of MA may reduce the number of sperm in the epididymis tail and has negative effects on reproductive system in male rats (34). Additionally, several experimental studies showed that administration of different dose of MA caused decreasing in the sperm count and normal morphology (35, 36).…”
Section: Discussionsupporting
confidence: 92%
“…The effects of MA on sperm chromatin also appear to be dose-depended as similar drugs which had more negative effects in high doses. Our findings were similar to the study by Alavi and colleagues which have demonstrated that frequent consumption of high dosage of MA may reduce the number of sperm in the epididymis tail and has negative effects on reproductive system in male rats (34). Additionally, several experimental studies showed that administration of different dose of MA caused decreasing in the sperm count and normal morphology (35, 36).…”
Section: Discussionsupporting
confidence: 92%
“…Recently, repeated methamphetamine administration caused a decrease in cell proliferation, induce apoptosis and reduce the proliferation/apoptosis ratio in male rat germ cells. Apoptotic cells were increased in both spermatogonia and primary spermatocytes after repeated administration of methamphetamine (Alavi et al, 2008). These findings may reflect that the genotoxic effect of methamphetamine seems to be involved especially in spermatogenesis (Yamamoto et al, 2002).…”
Section: Discussionmentioning
confidence: 91%
“…In this context, the effect of antioxidants in preventing damages resulting from free radicals has been studies in diabetic diseases [3]. Since the oxidative stress results from an imbalance between the production of free radicals and reactive oxygen species, antioxidant defence mechanism must be able to reduce the harmful effects of these aggressive agents [15].…”
Section: Discussionmentioning
confidence: 99%
“…Positive control sections were incubated with micrococcal nuclease or recombinant DNase1 to induce DNA strand breaks prior to labelling. Negative control sections were processed with label solution (without terminal transferase) [14,15].…”
Section: In Situ Germ Cell Apoptosis Detectionmentioning
confidence: 99%
See 1 more Smart Citation